APLIKASI PEMBELAJARAN BERBASIS WEB PADA TK MANGGA DI BAROS (Studi Kasus : TK Mangga, Desa Sukamanah, Kecamatan Baros, Kabupaten Serang, Banten) - Dianugrah Banuputri (2021)
The development of technology is increasingly advanced, computers have a very big role. TK Mangga has a process of teaching and learning activities consisting of letter recognition, reading iqro, counting, coloring and drawing pictures that still use 2 (two) dimensional drawing paper and a blackboard. The large number of students and the small number of teachers has an effect on reducing children's concentration in teaching and learning activities, so it is necessary to use web-based learning applications that interact to support teaching and learning activities between students and web-based teachers that are attractive and interactive. The benefits of this application are divided into 2 (two), namely the benefits for users which can increase the enthusiasm of students in teaching and learning activities and benefits for institutions. The waterfall model based on UML objects (usecase diagrams, activity diagrams, sequence diagrams and class diagrams) is used as a tool. Making information systems using PHP as a web programming language, Adobe Flash as an animation and audio manager, MySQL as a database server and testing of beb-based learning applications using black box testing. The result of the research is a web-based learning application that produces output in the form of teacher data reports and student data reports in the form of PDF and the results of the practice scores of each learning material that has been done by students who are not connected to the database, and teachers and parents of students can interact using the application Web Based Learning at TK Mangga in Baros.